2010
DOI: 10.1177/0192623309357946
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Oxidative Stress and Associated DNA Damage, Increased Proliferative Drive, and Altered Gene Expression in Rat Liver Produced by the Cholangiocarcinogenic Agent Furan

Abstract: Furan is a potent cholangiocarcinogen in rat by an as yet undefined mechanism. The risk to man remains unclear. Using a time-course stop study design, we have investigated the potential of furan to induce oxidative stress and DNA damage associated with inflammatory and regenerative responses in rat liver. Furan was administered via oral gavage (30 mg/kg b.w. 5 daily doses per week), and livers were analyzed at time points between eight hr and three months. A one-month recovery group previously treated for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 63 publications
(87 reference statements)
3
58
0
Order By: Relevance
“…Enhanced MDA levels were reported also in furan toxicity by Selmanoğlu et al (Selmanoğlu et al 2012). Recent studies about furan showed the generation of ROS and stimulation of lipid peroxidation supporting the function of oxidative stress in furan toxicity Hickling et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced MDA levels were reported also in furan toxicity by Selmanoğlu et al (Selmanoğlu et al 2012). Recent studies about furan showed the generation of ROS and stimulation of lipid peroxidation supporting the function of oxidative stress in furan toxicity Hickling et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Recent in vivo studies in furan treated animals showed reactive oxygen species (ROS) formation and stimulation of lipid peroxidation (LPO) promoting the function of oxidative stress in the toxicity of furan (31,32). Furan-caused oxidative stress adds substantially to liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furan-caused oxidative stress adds substantially to liver injury. Excessive ROS and raised LPO are some of the unwanted effects of furan (32). An increased MDA level, end product of LPO, is a major determinant of LPO (33).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The study of its genotoxic effect and the underlying mechanism thereof continues to be an active area of interest and still needs to be completely understood. [7] Notwithstanding these toxic effects, furan has been identified as representing a caged reactive functionality and seems to be an ideal template for the mild and selective generation of a reactive intermediate on demand. This furan-ring oxidation principle and the idea of using an easily incorporated and stable aromatic furan moiety as a substitute for a reactive unit has been elegantly used in the total synthesis of macrosphelides A and B [8] and (+)-Aspicillin.…”
Section: Introductionmentioning
confidence: 99%